Lazer e tecnologias da informação e comunicação (TICs): desafios para pensar a animação cultural na rede um estudo da comunidade Estudiolivre.org - Juliana de Alencar Viana (2010)
This dissertation describes and analyses the virtual community EstudioLivre.org, aiming at collecting elements to build intervention parameters to cultural animation on the Web. Recognizing Internet as an education, expression and leisure space, the techno-cultural approach seems to have a lack of discussion on the mediation question. It is not always clear that the cyberspace is full of antagonist forces. Turning theses relation into clear relations and contributing to a greater freedom of choice for its users is a concern that the animators shall mandatorily have. When one talks about mediation strategies, it is unavoidable thinking about the political role played by the social actors. To perceive the form in which people use technology means re-think methods brought in by this new investigation field for knowledge production. This study has as object to recognize new technologies of communication and information, especially the Internet, as a cultural product. In such way, which questions shall be raised by the new production logic at the cyberspace in order to our (re-)thinking of Cultural Animation? How Estúdio Livre thinks its strategies of mediation and how they help creating Internet interventions? To investigate several interests permeating the virtual environment means to give opportunities for new reflections about leisure and new technologies, as well as the formation and professional acting to an each time more connected society. Based on the assurance that the creation of communities at the cyberspace is a way to organize leisure practices in the Internet, it seems crucial to understand better this new organization, including a way to think the possible role of the cultural animator within this context. The method strategies used to collect data were constituted of virtual ethnography by means of participant observation and analyze of the items of EstudioLivre.org collection, blog, forum and wiki in the period from August 24 to October 2; questionnaire to track user profiles and further analyze of contents through the computer treatment in Atlas TI qualitative data analysis software. The analyze categories were permanence/participation; belonging; social relations; interactions and values. It was realized that the voluntary participation in the community is linked to other ethical-aesthetic parameter of relationship, which highlights a kind of social practice during the free time which refers to an understanding of leisure based on other foundations, differing from that exclusively pointed by the consumption and entertainment. The new production logic suggests alternative models to production and circulation of culture, inspired in free software concept and tools, providing for strategies of mediation against more comprehensive leisure options. The mediation of virtual activities shall contribute to clarify purposes and objectives, help to define values easing the development of different languages, creation and critical awareness of community identities. Approaching a possible technological practice, this paper seems to make clearer concrete elements to construction of intervention parameters to the Internet animator.